(untitled) - Ramsay, Jack (Hoboken, N.J., 2004)
Ramsay, whose 20-year career as a professional coach included a stint with the NBA title-winning Portland Trail Blazers, is currently a pro basketball analyst for ESPN. Although billed as a guide to leadership strategies learned from professional experience as well as his observation of outstanding players and other coaches, this manual is more a recollection of the sport Ramsay knows and loves. Many of the author's tips, directed to those who want to lead both on and off the court, include the need to set clear goals, develop self-confidence, make firm decisions and accept responsibility-certainly not original and often hackneyed. The text becomes more interesting when Ramsay backs up his advice with anecdotes about such basketball greats as Pat Riley, Michael Jordan and Magic Johnson. He credits Bird's ability, for example, to make a successful adjustment from college to NBA basketball to innate self-confidence honed by repetitive practice drills. Magic Johnson's HIV diagnosis motivated the player to maintain job readiness by eating right and exercising regularly, a plan that Johnson credits with keeping his disease under control and has inspired Ramsay's own pursuit of a healthy lifestyle. In the end, these leadership bromides, leavened by basketball stories, will interest mainly fans of the sport.
Keywords: Basketball coaches,Leadership,Huấn luyện viên bóng rổ,Lãnh đạo; United States,United States,Hoa Kỳ,Hoa Kỳ